Design, Synthesis, and Evaluation of Nitroxide Radical Derivatives Based on Rhein as Potential Anti-Aging Agents Targeting the Keap1-Nrf2 Pathway - Wang J; Peng X; Zhang X; Lin J; Zhang Q; Li J; Cui L; Zhao L (Drug Design, Development and Therapy, 2025)
Jie Wang,1,* Xuejing Peng,1,2,* Xinyue Zhang,1 Jia Lin,3 Qili Zhang,1,2 Jiaojiao Li,1 Longchen Cui,1 Lei Zhao1,2,4– 6 1College of Pharmacy, Gansu University of Chinese Medicine, Lanzhou, People’s Republic of China; 2Northwest Collaborative Innovation Center for Traditional Chinese Medicine Co-Constructed by Gansu Province & MOE of PRC, Gansu University of Chinese Medicine, Lanzhou, People’s Republic of China; 3College of Pharmacy, Gansu Health Vocational College, Lanzhou, People’s Republic of China; 4Key Laboratory of Chemistry and Quality of TCM of the College of Gansu Province, Gansu University of Chinese Medicine, Lanzhou, People’s Republic of China; 5Gansu Province Engineering Laboratory for TCM Standardization Technology and Popularization, Gansu University of Chinese Medicine, Lanzhou, People’s Republic of China; 6Gansu Pharmaceutical Industry Innovation Research Institute, Lanzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lei Zhao, College of Pharmacy, Gansu University of Chinese Medicine, 35 Dingxi East Road, Chengguan District, Lanzhou, 730000, People’s Republic of China, Tel +86 13893395136, Email zzyhx@gszy.edu.cn Longchen Cui, College of Pharmacy, Gansu University of Chinese Medicine, 35 Dingxi East Road, Chengguan District, Lanzhou, 730000, People’s Republic of China, Tel +86 13919908921, Email cuilongchen_1988@126.comPurpose: Targeting the crucial Keap1-Nrf2-ARE antioxidant pathway, we selected Rhein - a natural anthraquinone from traditional Chinese medicine with established Keap1-Nrf2 inhibitory activity as our lead compound. Through rational structural modification by incorporating nitroxide radicals at the 3-carboxyl position, we aimed to develop enhanced Keap1-Nrf2 modulators with anti-aging potential.Patients and Methods: A series of rhein nitroxide derivatives were synthesized, and their free radical scavenging activity was assessed in vitro using DPPH and ABTS methods. Compound 4b, demonstrating significant activity, was selected for further evaluation. Its effects on the survival of L02 hepatocytes under oxidative stress and the lifespan and stress tolerance of Caenorhabditis elegans (C. elegans) were investigated. Additionally, the impacts of 4b on antioxidant enzyme activity, malondialdehyde (MDA) levels, and reactive oxygen species (ROS) accumulation under oxidative stress were assessed. Molecular docking was conducted to analyze interactions between 4b and the Kelch domain of Keap1.Results: Compound 4b exhibited potent free radical scavenging activity, with IC50 values of 0.51 ± 0.09 mM against DPPH radicals and 0.12 ± 0.03 mM against ABTS radicals. It significantly improved the survival rate of L02 hepatocytes under oxidative stress, maintaining 95.42% viability (p < 0.01). In the C. elegans model, 4b extended the average lifespan and enhanced stress resistance, increasing GSH activity, reducing MDA content, and decreasing ROS accumulation. Molecular docking showed that 4b penetrates deeply into the Kelch domain of Keap1, forming stable interactions with key residues.Conclusion: Compound 4b demonstrates superior antioxidant and anti-aging effects compared to the parent compound rhein, representing a highly promising anti-aging candidate and Keap1-Nrf2 signaling pathway modulator with potential as a novel therapeutic agent for age-related diseases. Keywords: rhein, nitroxide radical, antioxidant, anti-aging, keap1-Nrf2 pathway